9(y-1)-7(2y+1)=10

Simple and best practice solution for 9(y-1)-7(2y+1)=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(y-1)-7(2y+1)=10 equation:


Simplifying
9(y + -1) + -7(2y + 1) = 10

Reorder the terms:
9(-1 + y) + -7(2y + 1) = 10
(-1 * 9 + y * 9) + -7(2y + 1) = 10
(-9 + 9y) + -7(2y + 1) = 10

Reorder the terms:
-9 + 9y + -7(1 + 2y) = 10
-9 + 9y + (1 * -7 + 2y * -7) = 10
-9 + 9y + (-7 + -14y) = 10

Reorder the terms:
-9 + -7 + 9y + -14y = 10

Combine like terms: -9 + -7 = -16
-16 + 9y + -14y = 10

Combine like terms: 9y + -14y = -5y
-16 + -5y = 10

Solving
-16 + -5y = 10

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '16' to each side of the equation.
-16 + 16 + -5y = 10 + 16

Combine like terms: -16 + 16 = 0
0 + -5y = 10 + 16
-5y = 10 + 16

Combine like terms: 10 + 16 = 26
-5y = 26

Divide each side by '-5'.
y = -5.2

Simplifying
y = -5.2

See similar equations:

| x+4=-5 | | -12=-3/7z | | 12x-6-12=7+12x-12 | | 2x+8+3x+-6=4findx | | A=j+p | | 6a-3=40 | | 9-2(7x-8x)=4x-3 | | C=5/9(95-32) | | 3x-7x+13x= | | -13+3=-39+17x | | -7c+22=6c-4 | | 3X+5FORX=8 | | 4(4x+7y)=69 | | y^3+15y^2+54y=0 | | 12x-6-1=27x+18-10x | | x^2-x^1/2=0 | | 5x=121 | | 6-t=1 | | -7x-6x-3=42 | | x^2=x^1/2 | | 5.6m+1.35=-51.85 | | t/3-7=11 | | .05(x)+.06(y)=612 | | 8x^4+4x^3-14x^2-9x+2=0 | | 5r+6t=3r-2 | | 6(x+6)=3(x+8) | | 2/7*3 | | 8x+11y=52 | | (3t+2)+(3t+3)+4=15 | | 3x-5+90=180 | | 3y+11=22 | | x^2=x^2-4 |

Equations solver categories